3D-Printed Filaments: Alginate Hydrogels With Cellulose Nanofibers as Functional Biomaterials for Tissue Engineering Applications - Mohamed Taha; Ragab Abouzeid; A. H. Abdelbaky Elbatran; M. Shehadeh; Husain Alfadhel; Wafa Mazi; Noha Omer; Mahmoud A. Abdelaziz; Amal T. Mogharbel; Hamouda M. Mousa (International Journal of Polymer Science)
This study is aimed at developing alginate hydrogel filaments enriched with TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl radical)–oxidized cellulose nanofibers (TOCNs) through 3D-printing techniques for application in bone tissue engineering. The filaments were designed to act as advanced biomaterials that support bone regeneration by combining alginate dissolved in phosphate ions with TOCNs, followed by extrusion into a calcium chloride solution. This process facilitated the cross-linking of alginate and in situ mineralization of calcium phosphate. The produced hydrogel filaments were characterized using a variety of techniques, including scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA). Additionally, in situ biomineralization tests confirmed the successful formation of apatite. Mechanical testing revealed a significant increase in tensile strength, ranging from 40 to 80 MPa, which underscores the improved structural integrity of the hydrogels. Rheological assessments demonstrated that the addition of TOCNs enhanced the viscoelastic properties of the filaments, making them more suitable for 3D-printing applications. Cytotoxicity tests further confirmed the biocompatibility of the scaffolds, showing enhanced cell proliferation. These results suggest that incorporating TOCNs into alginate hydrogels offers a promising approach to developing functional biomaterials in tissue engineering, particularly for bone regeneration applications.